Cell-free expression of RNA encoded genes using MS2 replicase. Issue 20 (30th September 2019) - Weise, Laura I; Heymann, Michael; Mayr, Viktoria; Mutschler, Hannes
Abstract: RNA replicases catalyse transcription and replication of viral RNA genomes. Of particular interest for in vitro studies are phage replicases due to their small number of host factors required for activity and their ability to initiate replication in the absence of any primers. However, the requirements for template recognition by most phage replicases are still only poorly understood. Here, we show that the active replicase of the archetypical RNA phage MS2 can be produced in a recombinant cell-free expression system. We find that the 3′ terminal fusion of antisense RNAs with a domain derived from the reverse complement of the wild type MS2 genome generates efficient templates for transcription by the MS2 replicase. The new system enables DNA-independent gene expression both in batch reactions and in microcompartments. Finally, we demonstrate that MS2-based RNA-dependent transcription-translation reactions can be used to control DNA-dependent gene expression by encoding a viral DNA-dependent RNA polymerase on a MS2 RNA template. Our study sheds light on the template requirements of the MS2 replicase and paves the way for new in vitro applications including the design of genetic circuits combining both DNA- and RNA-encoded systems.